Physician Asthma Management Practices in Canada - Robert Jin; Bernard CK Choi; Benjamin TB Chan; Louise McRae; Felix Li; Lisa Cicutto; Louis-Philippe Boulet; Ian Mitchell; Robert Beveridge; Eric Leith (Canadian Respiratory Journal)
OBJECTIVES: To establish national baseline information on asthma management practices of physicians, to compare the reported practices with the Canadian Consensus recommendations and to identify results potentially useful for interventions that improve physician asthma management practices.